2011 IEEE International Conference on IC Design &Amp; Technology 2011
DOI: 10.1109/icicdt.2011.5783216
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of the edge profile of interconnects on the occurrence of passivation cracks of plastic-encapsulated electronic power devices

Abstract: Deformations of metal interconnects, cracks in interlayer dielectrics and passivation layers in combination withplastic-packaging are still a major reliability concern for integrated circuit power semiconductors. In order to describe and understand the failure mechanism and its root cause, already a lot of work has been done in the past. However for the first time the impact of the edge profile of the power metal design on the amount of passivation cracks was investigated in detail. It was found that with a sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The conclusion was that the whole counterforce against the shear stress during TC, is built up by the edges of the passivation layer only [13]. In a further study, it was concluded that the shape of the metal edge profile could increase the resistance to crack formation significantly [15]. Still this was insufficient to eliminate failures completely.…”
Section: Fig 2 Typical Electronic Power Devicementioning
confidence: 97%
See 1 more Smart Citation
“…The conclusion was that the whole counterforce against the shear stress during TC, is built up by the edges of the passivation layer only [13]. In a further study, it was concluded that the shape of the metal edge profile could increase the resistance to crack formation significantly [15]. Still this was insufficient to eliminate failures completely.…”
Section: Fig 2 Typical Electronic Power Devicementioning
confidence: 97%
“…The shear stress is reaching a maximum with the cold cycles of the TC [6]. In earlier work it was shown that the edge profile of the metal interconnect has a significantly impact on the sensitivity for passivation crack formation [15]. With a sloped edge profile the force induced by the mold compound during the cold cycle of the TC is evenly distributed avoiding local stress concentrations.…”
Section: The Experimentsmentioning
confidence: 98%